2016
DOI: 10.1016/j.theriogenology.2015.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine and mammalian sperm: Lessons from the porcine model

Abstract: Biomedical nanotechnology allows us to engineer versatile nanosized platforms that are comparable in size to biological molecules and intracellular organelles. These platforms can be loaded with large amounts of biological cargo, administered systemically and act at a distance, target specific cell populations, undergo intracellular internalization via endogenous uptake mechanisms, and act as contrast agents or release cargo for therapeutic purposes. Over recent years, nanomaterials have been increasingly view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 77 publications
(9 reference statements)
0
18
0
Order By: Relevance
“…Although mice have been the model of choice for most ART studies, there has been a tendency to use bull and boar sperm to evaluate nanomaterial delivery efficiency and effects. Bull and boar sperm, as human sperm, do not need to be surgically retrieved and present similarities regarding morphology and maturation profiles (Barkalina et al, ). Characterization of sperm and identification of potential targets, such as proteins related to acrosome integrity (Cross & Watson, ) and genes linked to freezability (Vilagran et al, ), make the use of nanoparticles interesting for applications in studies involving sperm enrichment and sorting (Feugang, ).…”
Section: Nanotechnologymentioning
confidence: 99%
See 3 more Smart Citations
“…Although mice have been the model of choice for most ART studies, there has been a tendency to use bull and boar sperm to evaluate nanomaterial delivery efficiency and effects. Bull and boar sperm, as human sperm, do not need to be surgically retrieved and present similarities regarding morphology and maturation profiles (Barkalina et al, ). Characterization of sperm and identification of potential targets, such as proteins related to acrosome integrity (Cross & Watson, ) and genes linked to freezability (Vilagran et al, ), make the use of nanoparticles interesting for applications in studies involving sperm enrichment and sorting (Feugang, ).…”
Section: Nanotechnologymentioning
confidence: 99%
“…Mesoporous silica, quantum dots, iron oxide, zinc oxide, gold, and silver nanostructures have been shown to interact with cattle, human, mouse, and pig spermatozoa (Barkalina, Jones, Kashir, et al, ; Feugang et al, ; Feugang, Youngblood, Greene, Willard, & Ryan, ; Moretti et al, ; Taylor et al, ; Yoisungnern et al, ). In the pig, Barkalina et al () observed that mesoporous silica nanoparticles (MSNPs) functionalized with polyethileneimine (PEI) and aminopropyltriethoxysilane were able to stably bind one in five boar sperm with no negative effects on the main parameters of sperm function (total and progressive motility, motion parameters, viability, acrosome morphology, or DNA fragmentation index). Moreover, MSNPs loaded with proteins or nucleic acids were able to bind to the boar sperm and to the zona pellucida of mouse oocytes, demonstrating their potential for intracellular delivery.…”
Section: Nanotechnologymentioning
confidence: 99%
See 2 more Smart Citations
“…Exosomes, small extracellular membrane vesicles modulating cellular functionality, also deserve future attention, as they are substantially present in SP. It is speculated that exosomes secreted by the male reproductive tract play important roles in promoting and regulating sperm motility, protecting the sperm in the female genital tract and facilitating fertilizing ability [59].…”
Section: Seminal Plasma a Mine To Fully Discovermentioning
confidence: 99%